2023
DOI: 10.1186/s12889-023-15934-y
|View full text |Cite|
|
Sign up to set email alerts
|

Association between circadian syndrome and the prevalence of kidney stones in overweight adults: a cross-sectional analysis of NHANES 2007–2018

Abstract: Objective To explore the association between circadian syndrome (CircS) and the prevalence of kidney stones in overweight people. Materials and methods A cross-sectional analysis was conducted based on the NHANES 2007–2018. Overweight people aged ≥ 20 years were the target population. Three multivariable logistic regression models were built to examine the association between CircS and kidney stones. Subgroup analysis based on age, gender, and race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For example, Shi et al (2021) and Shi et al (2022 ) reported that Circs had a better predictive value than metabolic syndrome for cardiovascular disease in both Chinese and US adults. Additionally, studies also reported positive Circs associations with stroke ( Wang et al, 2022 ), kidney stones ( Xiao et al, 2023a ), and testosterone deficiency ( Xiao et al, 2023b ).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Shi et al (2021) and Shi et al (2022 ) reported that Circs had a better predictive value than metabolic syndrome for cardiovascular disease in both Chinese and US adults. Additionally, studies also reported positive Circs associations with stroke ( Wang et al, 2022 ), kidney stones ( Xiao et al, 2023a ), and testosterone deficiency ( Xiao et al, 2023b ).…”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis of Circadian Syndrome (CircS) is established by the presence of four or more of the following components, as delineated in prior studies[ 13 , 24 ]: a. Elevated triglycerides (≥ 150 mg/dL) or usage of lipid-lowering medications; b.Waist circumference of ≥ 102 cm in men and ≥ 88 cm in women. c. Elevated blood pressure (diastolic ≥ 85 mm Hg or systolic ≥ 130 mm Hg) or the use of antihypertensive medications.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the magnitude of associations between CircS and the prevalence and incidence of CVDs was higher than the magnitude of associations between MetS and CVDs [ 11 , 12 ]. Also, adults with CircS had higher odds of testosterone deficiency [ 13 ], stroke [ 14 ], and kidney stones [ 15 ] compared to counterparts who did not have CircS.…”
Section: Introductionmentioning
confidence: 99%